Theological Approach to Teaching Interactively and Empirically: Jesus as a Model - Tafonao, Talizaro - (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2023)
The approach taken by teachers in teaching has been an issue that is always discussed in the world of education. The limitations of Christian teachers in teaching provoke a reaction and judgment from various elements. Seeing this phenomenon, the author conducted a study of Jesus' approach in the Gospel of Matthew. The purpose of this research is to explain the attempt at a theological approach made by Jesus in the Gospel of Matthew. The research method used in this paper is a qualitative research method, the author examines various approaches taken by Jesus in the Gospel of Matthew. The analysis process carried out by the author is to use various trusted library and electronic sources to support the author's analysis. The results of this study found that there are two approaches taken by Jesus, namely interactive and empirical. Thus, the approach taken by Jesus in the Gospel of Matthew is still relevant to be used as a reference by Christian education teachers in teaching and educating in order to achieve learning objectives.